Caspase-3 is transiently activated without cell death during early antigen driven expansion of CD8(+) T cells in vivo. - Scott McComb; Rebecca Mulligan; Subash Sad (PLoS ONE)
Background CD8(+) T cell responses develop rapidly during infection and are swiftly reduced during contraction, wherein >90% of primed CD8(+) T cells are eliminated. The role of apoptotic mechanisms in controlling this rapid proliferation and contraction of CD8(+) T cells remains unclear. Surprisingly, evidence has shown non-apoptotic activation of caspase-3 to occur during in vitro T-cell proliferation, but the relevance of these mechanisms to in vivo CD8(+) T cell responses has yet to be examined. Methods and findings We have evaluated the activity of caspase-3, a key downstream inducer of apoptosis, throughout the entirety of a CD8(+) T cell response. We utilized two infection models that differ in the intensity, onset and duration of antigen-presentation and inflammation. Expression of cleaved caspase-3 in antigen specific CD8(+) T cells was coupled to the timing and strength of antigen presentation in lymphoid organs. We also observed coordinated activation of additional canonical apoptotic markers, including phosphatidylserine exposure. Limiting dilution analysis directly showed that in the presence of IL7, very little cell death occurred in both caspase-3(hi) and caspase-3(low) CD8(+) T cells. The expression of active caspase-3 peaked before effector phenotype (CD62L(low)) CD8(+) T cells emerged, and was undetectable in effector-phenotype cells. In addition, OVA-specific CD8(+) cells remained active caspase-3(low) throughout the contraction phase. Conclusions Our results specifically implicate antigen and not inflammation in driving activation of apoptotic mechanisms without cell death in proliferating CD8(+) T cells. Furthermore, the contraction of CD8(+) T cell response following expansion is likely not mediated by the key downstream apoptosis inducer, caspase-3.